Post-exercise branched chain amino acid supplementation does not affect recovery markers following three consecutive high intensity resistance training bouts compared to carbohydrate supplementation. Issue 1 (26th July 2016) - Kephart, Wesley C.; Mumford, Petey W.; McCloskey, Anna E.; Holland, A. Maleah; Shake, Joshua J.; Mobley, C. Brooks; Jagodinsky, Adam E.; Weimar, Wendi H.; Oliver, Gretchen D.; Young, Kaelin C.; Moon, Jordan R.; Roberts, Michael D.
Abstract: Background: Amino acid supplementation has been shown to potentially reduced exercise-induced muscle soreness. Thus, the purpose of this study was to examine if branched chain amino acid and carbohydrate (BCAACHO) versus carbohydrate-only sports drink (CHO) supplementation attenuated markers of muscle damage while preserving performance markers following 3 days of intense weight training. Methods: Healthy resistance-trained males ( n  = 30) performed preliminary testing (T1) whereby they: 1) donated a baseline blood draw, 2) performed knee extensor dynamometry to obtain peak quadriceps isometric and isokinetic torque as well as electromyography (EMG) activity at 60°/s and 120°/s, and 3) performed a one repetition maximum (1RM) barbell back squat. The following week participants performed 10 sets x 5 repetitions at 80 % of their 1RM barbell back squat for 3 consecutive days and 48 h following the third lifting bout participants returned for (T2) testing whereby they repeated the T1 battery. Immediately following and 24 h after the three lifting bouts, participants were randomly assigned to consume one of two commercial products in 600 mL of tap water: 1) BCAAs and CHO (3 g/d L-leucine, 1 g/d L-isoleucine and 2 g/d L-valine with 2 g of CHO; n  = 15), or 2) 42 g of CHO only ( n  = 15). Additionally, venous blood was drawn 24 h following the first and second lifting bouts and 48 h following the third bout to assess serum myoglobin concentrations, and a visual analog scale was utilized prior, during, and after the 3-d protocol to measure subjective perceptions of muscular soreness. Results: There were similar decrements in 1RM squat strength and isokinetic peak torque measures in the BCAA-CHO and CHO groups. Serum myoglobin concentrations ( p  = 0.027) and perceived muscle soreness ( p  < 0.001) increased over the intervention regardless of supplementation. A group*time interaction was observed for monocyte percentages ( p  = 0.01) whereby BCAA-CHO supplementation attenuated increases in this variable over the duration of the protocol compared to CHO supplementation. Conclusion: BCAA-CHO supplementation did not reduce decrements in lower body strength or improve select markers of muscle damage/soreness compared to CHO supplementation over three consecutive days of intense lower-body training.